2023
DOI: 10.1111/1475-6773.14168
|View full text |Cite
|
Sign up to set email alerts
|

Growing a rural family physician workforce: The contributions of rural background and rural place of residency training

Abstract: ObjectiveTo determine the distinct influences of rural background and rural residency training on rural practice choice among family physicians.Data Sources and Study SettingWe used a subset of The RTT Collaborative rural residency list and longitudinal data on family physicians from the American Board of Family Medicine National Graduate Survey (NGS; three cohorts, 2016–2018) and American Medical College Application Service (AMCAS).Study DesignWe conducted a logistic regression, computing predictive marginals… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…There is a significant body of research on the impact of residency training on the choice to practice in rural areas [ 41 , 42 ] Since this study was conducted in Spain, the results can contribute to a better understanding of whether there are other important factors that have not been previously studied. Most of the residents defined the training programme as rewarding and having significant learning opportunities.…”
Section: Discussionmentioning
confidence: 99%
“…There is a significant body of research on the impact of residency training on the choice to practice in rural areas [ 41 , 42 ] Since this study was conducted in Spain, the results can contribute to a better understanding of whether there are other important factors that have not been previously studied. Most of the residents defined the training programme as rewarding and having significant learning opportunities.…”
Section: Discussionmentioning
confidence: 99%
“…While uneven geographic distribution of oncology specialists has been established, more needs to be done to understand disparities for specific cancer types and oncology specialties . These rural disparities may be influenced by fewer training programs in rural areas, debt and salary concerns, or simply by limited access to specialized equipment to conduct complex therapy …”
Section: Discussionmentioning
confidence: 99%
“… 10 , 16 , 17 These rural disparities may be influenced by fewer training programs in rural areas, debt and salary concerns, or simply by limited access to specialized equipment to conduct complex therapy. 10 , 18 …”
Section: Discussionmentioning
confidence: 99%
“…3,4,8,9,11,13 There is substantial evidence for other health care professionals, particularly physicians, that rural training experiences are effective in recruiting, appropriately preparing, and retaining clinicians. [13][14][15][16][17] A few studies have demonstrated that rural and underserved communityfocused training for behavioral health trainees can increase interest in and actual recruitment to work in rural and underserved settings 11,18 ; however, there is a dearth of research investigating the effects of training on behavioral health clinicians' preparedness, successes, and retention in rural underserved communities.…”
Section: Introductionmentioning
confidence: 99%